WHO BENEFITS FROM FUNDS OF HEDGE FUNDS? A CRITIQUE OF ALTERNATIVE ORGANIZATIONAL STRUCTURES IN THE HEDGE FUND INDUSTRY (II) - Yang CAO (Business Excellence and Management, 2012)
This paper provides a critique of alternative organizational structures in the hedge fund industry. Our critique is facilitated by several stylized models describing alternative industry structures. The models include: (1) An insideonly hedge fund model; (2) A straddling hedge fund model; (3) A straddling “feeder” fund of funds (FOF) hedge fund model; (4) A stand-alone outside hedge fund; and (5) An outside “feeder” FOF hedge fund model. Our discussion of these models, which centers on benefits vs. fundamental problems related to illiquidity, information asymmetry, and conflicts of interest, leads to several hypotheses about the differential characteristics and return performance of both individual hedge funds and FOFs. We test as many of these hypotheses as data availability allows, and evidence is consistent with these hypotheses. Regarding characteristics, we predict that some hedge funds and FOFs will have greater leverage and/or more restrictive withdrawal policies than others, and evidence is consistent with these predictions. Regarding return performance, we predict that certain hedge funds, and FOFs in general, will have relatively poor return performance, and evidence is consistent.